New Oppiidae (Acari: Oribatida) from the Golden Gate Highlands National Park in South Africa - Hugo-Coetzee, Elizabeth A. (Zootaxa, 2014)
A checklist of Oppiidae sampled at Golden Gate Highlands National Park in central South Africa is provided. Twelve genera and 17 species were recorded of which one species, Arcoppia fenestralis, is recorded from South Africa for the first time. One new subgenus and six new species were identified and are described. The new species are Brachioppia louwi sp. nov., Brachioppiella (B.) dawidi sp. nov., Brachioppiella (B.) goblina sp. nov., Kokoppia mandelai sp. nov., Lanceoppia (L.) scytheae sp. nov., Oppiella (Q.) goldengatensis sp. nov.. Oppiella (Quattoppiella) subgen. nov. is characterized by the absence of costulae on the prodorsum and having four pairs of genital setae.